Prosthodontic rehabilitation of a complete edentulous patient with mandibular prognathism: A case report - Leonardo Jaya Setiadi Tanumiharja; Marvin Jaya Setiadi Tanumiharja; Winny Suwindere; Imanuella Stevanie Jovanca Situmorang; Metta Sari Sutanto; Joni Putra Nasution (Institute of Computer Science (IOCS), 2026)
Background: Rehabilitation of completely edentulous patients with mandibular prognathism remains a clinical challenge because abnormal maxillomandibular relationships compromise denture retention, stability, occlusion, and function. Evidence describing prosthodontic management of this condition is still limited. Objective: To describe the prosthodontic rehabilitation of a completely edentulous patient with mandibular prognathism using complete dentures with an edge-to-edge tooth arrangement. Case Presentation: A 57-year-old male presented with complete edentulism for approximately ten years and complained of impaired mastication and speech. Clinical examination revealed a prognathic mandibular relationship with a 2-mm mandibular deviation to the right and severe alveolar ridge resorption. Treatment: The patient underwent conventional complete denture fabrication including preliminary and final impressions, jaw relation recording, semi-adjustable articulator mounting, and edge-to-edge anterior tooth arrangement to accommodate the skeletal discrepancy. Results: One month after denture insertion, clinical evaluation demonstrated satisfactory denture retention and stability without mucosal ulceration or occlusal interference. The patient reported improved chewing ability, speech, aesthetics, and overall satisfaction with the prosthesis. Clinical Significance: Edge-to-edge tooth arrangement can be considered a practical treatment option for complete denture rehabilitation in selected patients with mandibular prognathism, providing acceptable retention, stability, and functional outcomes despite unfavorable jaw relationships.